UJI AKTIVITAS BAKTERI PENAMBAT NITROGEN DAN PENGHASIL IAA DARI RIZOSFER TANAMAN KEDELAI ( Glycine max L.) - saida saida; Puspitasari Puspitasari; Aminah Aminah (Percetakan Umi Toaha Makassar, 2022)
This study aims to examine the activities of nitrogen-fixing bacteria and Indole Acetic Acid (IAA)-producing bacteria from the soybean plant rhizosphere. This research was conducted at the Laboratory of Plant Pests and Diseases, Faculty of Agriculture, Universitas Muslim Indonesia (UMI), Makassar. Analysis of the sample N fastening test was carried out at the Laboratory of Soil and Conservation, Faculty of Agriculture, UMI, Makassar. Analysis of the IAA test sample was carried out at the Laboratory of Plant Pests and Diseases, Faculty of Agriculture, Hasanuddin University, Makassar, from May to July 2021. This study used a Completely Randomized Design (CRD) method. The isolates tested were isolates obtained from soybean roots, namely isolate 2.2, isolate 2.3 and isolate 3.2. Of the three isolates, each was replicated three times, so that there were nine replications. The obtained data was then analyzed using the Anova test.The results showed that isolate 3.2 had a higher nitrogen fixation ability, which was 20.31% compared to isolate 2.2 and isolate 2.3. The density level of isolate 2,3 tended to be higher, with an absorbance of 0.43 and the ability to produce IAA at 6.61 ppm.